Formulasi Sediaan Lipstik Dari Ekstrak Kulit Buah Manggis (Garcinia mangostana L.) - Sapitri, Desti Amalia; Irtawidjajanti, Sri; Ambarwati, Neneng Siti Silfi (Universitas Pahlawan Tuanku Tambusai, 2025)
Lipstick is a cosmetic product applied to the lips and is likely to be ingested along with saliva, food, or drink. The repeated use of harmful synthetic dyes in lipstick can have adverse effects on health. Therefore, safer natural dye alternatives are needed, such as mangosteen fruit peel extract (Garcinia mangostana L.), which contains anthocyanin compounds as natural dyes due to the purple-red color of the mangosteen fruit peel. This study aims to formulate and evaluate the physical quality of lipstick using natural dyes from mangosteen peel extract based on the standards SNI 16-4769-1998 and SNI 16-4399-1996. The method used was laboratory experimentation with maceration techniques using 96% ethanol as a solvent. Three lipstick formulas were created with varying concentrations of extract: F1 (3 grams), F2 (5 grams), and F3 (7 grams). The quality evaluation of the formulations included organoleptic testing, pH measurement, stability testing, homogeneity testing, adhesion testing, and melting point testing. The results showed that all formulas had good color, texture, aroma, and shape stability. Formulas 2 and 3 met the lip pH requirements (4.5-7), while formula 1 was below the safe limit, showing a pH value of 4.41. All three formulas showed good homogeneity with no coarse particles, adhesion of more than 4 seconds, and melting point that met the standard (52-53.5°C). Based on these evaluation parameters, it can be concluded that Formula 2 and Formula 3 are the most optimal formulations and have the potential to be further developed as cucumber fruit extract-based lip balm.